2020
DOI: 10.1039/d0ta01741h
|View full text |Cite
|
Sign up to set email alerts
|

Dopant arrangements in Y-doped BaZrO3 under processing conditions and their impact on proton conduction: a large-scale first-principles thermodynamics study

Abstract: The proton conductivity maximum in doped BaZrO3 is explained by a percolation vs. many-body trapping picture using first-principles thermodynamics calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 66 publications
2
31
2
Order By: Relevance
“…This simple assumption is only based on the high sintering temperature of BaZrO3 above 1873 K. In addition, supercells with random distribution of Y-Y pairs were also employed in one of the previous reports [18] to roughly estimate the association effect of Y dopants [20] on the proton diffusivity. Kasamatsu et al have recently reported the thermal equilibrium configurations of Y dopants and O vacancies in the wide temperature range (600-2500 K), which were determined by a first-principles thermodynamic sampling simulation based on the replica exchange Monte Carlo (RXMC) method [21]. They claimed that the Y configuration in Y-doped BaZrO3 does not reach the random configuration even at the highest temperature, suggesting that the above assumption concerning the Y configuration in the crystal could be too simple.…”
Section: Toyoura Et Al Theoretically Clarified the Detailed Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple assumption is only based on the high sintering temperature of BaZrO3 above 1873 K. In addition, supercells with random distribution of Y-Y pairs were also employed in one of the previous reports [18] to roughly estimate the association effect of Y dopants [20] on the proton diffusivity. Kasamatsu et al have recently reported the thermal equilibrium configurations of Y dopants and O vacancies in the wide temperature range (600-2500 K), which were determined by a first-principles thermodynamic sampling simulation based on the replica exchange Monte Carlo (RXMC) method [21]. They claimed that the Y configuration in Y-doped BaZrO3 does not reach the random configuration even at the highest temperature, suggesting that the above assumption concerning the Y configuration in the crystal could be too simple.…”
Section: Toyoura Et Al Theoretically Clarified the Detailed Interactmentioning
confidence: 99%
“…This was repeated twice corresponding to the two independent RXMC runs in Ref. [21]. This means that 72 supercell models consisting of 9×9×9 unit cells were prepared for each (xY, Tsinter) pair to be used in diffusivity calculations.…”
Section: Y Configurationsmentioning
confidence: 99%
“…[20]. On the other hand, Kasamatsu et al have recently reported the thermal equilibrium configurations of Y dopants and O vacancies in the wide temperature range (600-2500 K), which were determined by a first-principles thermodynamic sampling simulation based on the replica exchange Monte Carlo (RXMC) method [21]. They claimed that the Y configuration in Y-doped BaZrO 3 does not reach the random configuration even at the highest temperature, suggesting that the above assumption concerning the Y configuration in the crystal could be too simple.…”
Section: Toyoura Et Al Theoretically Clarified the Detailed Interactmentioning
confidence: 99%
“…As noted above, RXMC sampling of Y dopants on Zr sites and O vacancies configurations were performed in Ref. [21] by one of the authors. The sampling was performed within a 3×3×3 cubic perovskite supercell at varying Y concentrations (x Y = 0.07, 0.15, 0.22, 0.30) and at 16 temperatures between T = 600 K and T = 2500 K. The calculations were repeated twice resulting in two independent equilibrium ensembles of 1400 configurations for each (x Y , T) pair.…”
Section: Y Configurationsmentioning
confidence: 99%
See 1 more Smart Citation